Woman’s Identity Crisis in the Clash of Cultures: A Study of Betool Khedairi’s Novel: A Sky So close (Journal of the College of Education for Women, 2019)
This paper is an attempt to clarify the impact of Postcolonialism, one of the mostchallenging fields of study that has emerged in recent years, on representations of women inonce-colonised countries and in Western locations. It discusses the influence of culturaldifferences on the status and identity of a woman who experience ‗multiculturalism‘. Thestudy is an analytical reading of a contemporary novel written by the Iraqi writer Betool Al-Kudairi. The emphasis lies on the clash between two different cultures and traditionsrepresented by the British mother and the Iraqi father and its effect on the life and identity ofthe protagonist. The main focus is on idea of ‗hybrid identity‘ and the absence of the sense ofbelonging. A Sky so Close is a close look into the clash between East and West and into thesoul of a woman formed by two cultures yet fully accepted by neither.